2003
DOI: 10.1001/archpedi.157.9.926
|View full text |Cite
|
Sign up to set email alerts
|

Maternal-Child Feeding Patterns and Child Body Weight

Abstract: Background: Certain mother-child feeding patterns (MCFPs) may promote childhood obesity and/or disordered eating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
66
0
5

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 30 publications
2
66
0
5
Order By: Relevance
“…Study designs that look at differences between feeding styles of African-American, Caucasian, Hispanic and other ethnic groups are necessary to fully understand the influence of culture on these behaviors. 27 In sum and within the limits of this study, maternal perceived responsibility for child feeding, perception of child overweight and monitoring of child fat intake appear to be components of the shared home environment, whereas maternal concerns about child weight, restriction of child eating and encouragement of child eating appear to be components of the non-shared environment. Differences in the maternal concern about child weight and eating encouragements are associated with differences in sibling weight status.…”
mentioning
confidence: 57%
“…Study designs that look at differences between feeding styles of African-American, Caucasian, Hispanic and other ethnic groups are necessary to fully understand the influence of culture on these behaviors. 27 In sum and within the limits of this study, maternal perceived responsibility for child feeding, perception of child overweight and monitoring of child fat intake appear to be components of the shared home environment, whereas maternal concerns about child weight, restriction of child eating and encouragement of child eating appear to be components of the non-shared environment. Differences in the maternal concern about child weight and eating encouragements are associated with differences in sibling weight status.…”
mentioning
confidence: 57%
“…(Previous studies have not found an effect of SES on feeding practice: e.g. Faith et al, 2003;Patrick et al, 2005). All families from each of the nurseries were given questionnaires by nursery staff if they had a child over 1 year of age.…”
Section: Methods Participantsmentioning
confidence: 99%
“…Such a model highlights that parent and child BMI should be taken into account in the assessment of the relationship between parental eating and feeding practices. However, whilst some work has suggested that the relationships between parental eating psychopathology and controlling feeding practices are independent of child actual or perceived weight (Tiggeman & Lowes, 2002), and that maternal and child BMI are unrelated to maternal-child feeding patterns (Faith et al, 2003), others suggest that aspects of controlling feeding practices can explain significant amounts of variance in children's adiposity (e.g. Spruijt-Metz, Lindquist, Birch, Fisher & Goran, 2002).…”
Section: Maternal and Paternal Controlling Feeding Practices With Malmentioning
confidence: 99%
“…Research shows a strong correlation between parental and child obesity, particularly among mothers and their children. [12][13][14] Moreover, there is evidence of strong associations between parenting practices and children's eating habits, physical activity, and weight status, suggesting that the promotion of effective parenting is critical for the prevention of obesity. [15][16][17] Maccabi Health Care Services (MHS) is the second largest health maintenance organization in Israel, providing primary care services to 2 million beneficiaries throughout the country.…”
mentioning
confidence: 99%